Single Common Powertrain Lubricant Development - Brandt, Adam C; Frame, Edwin A; Hansen, Greg A; Warden, Robert W; Comfort, Allen S (2012)
The US Army has a desire to consolidate multiple MIL specification fluids into a single specification, or Single Common Powertrain Lubricant (SCPL). The application of this fluid would include engine lubrication, power shift transmission operation, and limited use in hydraulic systems, and must be designed to operate in ambients ranging from low temperature arctic, to high temperature desert type conditions. The U.S. Army TARDEC Fuels and Lubricants Research Facility (TFLRF) located at Southwest Research Institute (SwRI) has aided TARDEC in the initial development of the SCPL. A request for experimental products was issued to industry, and 4 potential SCPL candidates were received and tested in military applications. Testing included high temperate endurance in the General Engine Products 6.5L(T) diesel engine to asses engine protection and oil performance at elevated temperatures, multiple industry standardized transmission tests (Allison C4, Caterpillar TO-4, John Deere JDQ) to asses frictional performance and driveline durability, and quantification of fuel consumption improvement over standard military oils through viscosity reduction in the SCPL. Two strong candidate lubricants were identified during testing, and have been jointly selected by TARDEC and SwRI for further revisions and testing.